2014
DOI: 10.1089/sur.2013.076
|View full text |Cite
|
Sign up to set email alerts
|

Macrolides Are Associated with a Better Survival Rate in Patients Hospitalized with Community-Acquired But Not Healthcare-Associated Pneumonia

Abstract: "Macrolides are associated with a better survival rate in patients hospitalized with community-acquired but not healthcareassociated pneumonia. " Surgical Infections.15,3. 283-289. (2014 Background: Macrolide-based treatment has been associated with survival benefit in patients hospitalized with community-acquired pneumonia (CAP). However, the influence of macrolide therapy in all patients hospitalized with pneumonia, including healthcare-associated pneumonia (HCAP), is unclear.Methods: Analysis of a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This result suggests that macrolide effects other than appropriateness of antibiotics might affect mortality . Second, although BLM efficacy was questionable in patients with HCAP, our results suggest that BLM may be effective in patients at low risk for CAP‐DRPs in HCAP as well as those in CAP. This is additional evidence in favour of unified antibiotic selection in both CAP and HCAP.…”
Section: Discussionmentioning
confidence: 78%
“…This result suggests that macrolide effects other than appropriateness of antibiotics might affect mortality . Second, although BLM efficacy was questionable in patients with HCAP, our results suggest that BLM may be effective in patients at low risk for CAP‐DRPs in HCAP as well as those in CAP. This is additional evidence in favour of unified antibiotic selection in both CAP and HCAP.…”
Section: Discussionmentioning
confidence: 78%
“…Despite this, beneficial effects have been observed in clinical practice with their use, including earlier resolution of VAP, earlier extubation, and a reduced risk of death from sepsis and multiple organ dysfunction [29,30]. An RCT of macrolide therapy conducted in gram-negative sepsis due to extrapulmonary infection failed to meet its primary endpoint of reduced mortality [31].…”
Section: 2mentioning
confidence: 99%
“…Because patients with CAP and HCAP can have overlapping exposures in the community, some have advocated for the use of macrolides or fluoroquinolones as part of the empiric regimen for patients with HCAP . In one single‐centred experience, 65% of patients with HCAP were treated with a macrolide despite no available guideline recommendation to support this practice . This is owing to the potential for atypical pathogens and the consequences of inadequate coverage of these microbes .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…One recent meta‐analysis (23 studies, n = 137,574) indicated no benefit of macrolide therapy with regard to 30‐day mortality when only randomized controlled trials were evaluated (4·6% vs. 4·1% non‐users, P = 0·66) or guideline‐recommended therapy was provided (5·3% vs. 5·8% non‐users, P = 0·22) . The potential benefit of macrolides in reducing in‐hospital mortality for patients with CAP has not been consistently demonstrated, and based on the limited evidence, there does not appear to be a benefit in patients with HCAP …”
Section: What Is New and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation